Step by step solution :
Step 1 :
Equation at the end of step 1 :
(2 • (x - 10) + 4) - (2 - 6x) = 0
Step 2
Pulling out like terms :
Pull out like factors :
8x - 18 = 2 • (4x - 9)
Equation at the end of step 3 :
2 • (4x - 9) = 0
Step 4 :
Equations which are never true
Solve : 2 = 0
This equation has no solution.
A a non-zero constant never equals zero.
Solving a Single Variable Equation :
Solve : 4x-9 = 0
Add 9 to both sides of the equation :
4x = 9
Divide both sides of the equation by 4:
x = 9/4 =
2.250